Gelatin extraction from the Bangladeshi pangas catfish (pangasius pangasius) waste and comparative study of their physicochemical properties with a commercial gelatin - Barmon, Liton Chandra; Sikder, Md. Belal Hossain; Ahmad, Iftekhar; Shourove, Jahid Hasan; Rashid, Shah Samiur; Aizi Nor Mazila, Ramli (Penerbit Universiti Malaysia Pahang, 2021)
Production of gelatin from the aquatic source is gradually replacing the mammalian sources because of some socio-cultural and religious issues. The Pangasius pangasius catfish is a native species and very popular in Bangladesh due to their availability and cheap price. The perspective of this study was to extract the gelatin from the skin and bones of this catfish and compare them with commercial gelatin. Gelatin was extracted by applying the acid-base extraction process and the resultant gelatins were evaluated based on some physical properties. The gelatin yield was found significantly higher from the skin sample (10.85±0.93%) than the bone (5.23±0.39%) of Pangasius. The extracted skin gelatin had higher moisture and fat content than the bone and Commercial gelatin, while the ash content was significantly higher in bone gelatin. Protein content was noted in skin gelatin (81.34±3.45%), bone gelatin (73.44±2.58%), Where commercial gelatin (92.38±3.89%). Skin gelatin exerted significantly higher (p<0.05) viscosity (4.62±0.3 mPa.s) than the extracted bone gelatin (3.11±.24 mPa.s) and lower than the commercial gelatin (5.76±0.34 mPa.s). The melting and setting temperature of this catfish skin and bone gelatin were very near to each other and significantly lower than the commercial gelatin. Skin gelatin had exerted higher water holding capacity (2.36±0.11 ml/g), fat binding capacity (3.23±0.05 ml/g), foaming capacity ratio (1.88±0.07), and foam stability (1.51±0.04). Both the skin and bone gelatins were acidic. In this comparative study, it was noticed that the skin gelatin had better physical properties than the bone gelatin of native Pangasius catfish. Pangasius skin may be recognized as a potential aquatic source of edible gelatin with good yield and desirable physical properties comparing with commercial gelatin.